Machine Perfusion of Extended Criteria Donor Organs: Immunological Aspects - Kvietkauskas, Mindaugas; Leber, Bettina; Strupas, Kestutis; Stiegler, Philipp; Schemmer, Peter (Frontiers in Immunology, 2020)
Due to higher vulnerability and immunogenicity of extended criteria donor (ECD) organs used for organ transplantation (Tx) the discovery of new treatment strategies, involving tissue allorecognition pathways, is important. The implementation of machine perfusion (MP) led to improved estimation of the organ quality and introduced the possibility to achieve graft reconditioning prior to Tx. A significant number of experimental and clinical trials demonstrated increasing support for MP as a promising method of ECD organ preservation compared to classical static cold storage. MP reduced ischemia-reperfusion injury resulting in protection from inadequate activation of innate immunity. However, there are no general agreements on MP protocols and clinical application is limited. The objective of this comprehensive review is to summarize literature on immunological effects of MP of ECD organs, based on experimental studies and clinical trials.